Are Lactobacillus salivarius G60 and inulin more efficacious to treat patients with oral halitosis and tongue coating than the probiotic alone and placebo? A randomized clinical trial. Issue 6 (19th December 2019) - Mousquer, Camila Rafaela; Della Bona, Alvaro; Milani, Daiane Cristina; Callegari‐Jacques, Sidia Maria; Ishikawa, Karin; Mayer, Marcia Pinto Alves; Rösing, Cassiano Kuchenbecker; Fornari, Fernando
Abstract: Background: The combination of probiotics and prebiotics might be useful to treat oral halitosis. The aim of this study was to assess the effect of Lactobacillus salivarius G60 (LS) and inulin on oral halitosis and tongue coating. Methods: In this double‐masked, randomized, phase II clinical trial, 45 patients (aged 35 ± 15 years, 66% female) with oral halitosis and tongue coating were allocated to three treatment groups (n = 15) using gums of oral dissolution (one gum every 12 hours) for 10 days. Each gum contained LS (1 billion colony forming units [CFUs]) + inulin (1 g), LS (1 billion CFU) or placebo. Primary outcomes were organoleptic test, Halimeter, and tongue coating, whereas secondary outcomes were quality of life (QOL) and treatment safety. Generalized linear models were used, adjusting for age and sex. In vitro tests were performed to verify whether LS interacts with inulin and whether LS inhibits the growth of Porphyromonas gingivalis and Prevotella intermedia . Results: Forty‐four patients (97%) completed the study. Patients treated with LS + inulin showed greater reduction in halitosis measured by Halimeter compared with placebo (adjusted post‐intervention average: 96.7 versus 142.5 ppb; P = 0.003), whereas LS and placebo did not differ (115.7 versus 142.5 ppb; P = 0.097). Organoleptic measurements and coating index showed a similar decrease for all groups. QOL improved in patients treated with LS + inulin compared with placebo ( P = 0.029). Side effects were mild and transient in all groups. LS did not metabolize inulin but inhibited the growth of P. gingivalis and P. intermedia after 72 hours. Conclusions: Treatment with L. salivarius G60 combined or not with inulin showed significant decrease in the outcomes organoleptic test, Halimeter, and coating index, improving oral halitosis. However, no significant difference was obtained between the groups.